Psychoeducation for Fibromyalgia Syndrome: A Systematic Review of Emotional, Clinical and Functional Related-Outcomes - Carmen M. Galvez-Sánchez; Casandra I. Montoro (Behavioral Sciences, 2023)
Fibromyalgia Syndrome (FMS) is a chronic condition of widespread pain accompanied by several symptoms such as stiffness, fatigue, sleep problems, depression, anxiety, and cognitive deficits. To date, there is no specific treatment for FMS. The European League Against Rheumatism, and the majority of the international recommendations for managing FMS, has claimed psychoeducational intervention as the first step in FMS treatment for adequate symptoms management. However, scientific studies in this regard are scarce, diverse, and with contradictory findings. Results integration from analogous studies could provide a clear presentation of the real clinical value of psychoeducation in FMS. Therefore, the current systematic review aims at exploring the effect of psychoeducation on emotional, clinical, and functional symptoms of FMS patients and encourages researchers towards psychoeducation’s procedure optimization and systematization. The systematic review was conducted according to the guidelines of the Cochrane Collaboration and PRISMA statements. The selected articles were evaluated using the Cochrane risk of bias (ROB) assessment tool. The selected articles were extracted from PubMed, Scopus, and Web of Science databases. The literature search identified 11 studies eligible for the systematic review. The ROB evaluation revealed that 2 of the 11 studies showed a low quality, the other 2 had a moderate quality, and the remaining 7 studies exhibited a high quality. Results showed that psychoeducation is generally included as an important first therapeutic step in multicomponent treatments for FMS. Moreover, psychoeducation generally seems to be quite beneficial in reducing emotional (i.e., number of days feeling emotionally well, general anxiety, depression levels, etc.) and clinical symptoms (levels of fatigue, morning stiffness, pain intensity, etc.), as well as increasing functional status (i.e., general physical function, morning fatigue, stiffness, etc.). Despite that psychoeducation´s clinical benefits are highlighted, there is scarce amount of research on psychoeducation beyond its usefulness as part of multicomponent treatments.